Chapter Una montagna di debiti. L'Italia e la gestione del debito pubblico tra le due guerre - Astore, Marianna (Studi e saggi, 2020)
The surge in public debt during the recent pandemic crisis has made high debt a prominent policy issue. Italy is an interesting case study since it has experienced high levels of debt for a significant part of its history. This article revisits the history of Italian public debts in the inter-war period. Italy emerged from WWI with public debt that peaked around 160 percent of GDP. In the mid-1920s a significant reduction of public debt occurred, in concomitance with a regime of fiscal austerity and two restructuring agreements that wiped more than 80 percent of Italian foreign debts. By the early 1930s, the US reaction to the Great Depression that opposed any form of international cooperation, led to an Italian default on war debts in 1934 and a move toward autarky.